Near-infrared spectroscopy for structural bone assessment: a potential point-of-care tool. (7th April 2023) - Sharma, Varun J.; Adegoke, John A.; Afara, Isaac O.; Stok, Kathryn; Poon, Eric; Gordon, Claire L.; Wood, Bayden R.; Raman, Jaishankar
Abstract : Aims: Disorders of bone integrity carry a high global disease burden, frequently requiring intervention, but there is a paucity of methods capable of noninvasive real-time assessment. Here we show that miniaturized handheld near-infrared spectroscopy (NIRS) scans, operated via a smartphone, can assess structural human bone properties in under three seconds. Methods: A hand-held NIR spectrometer was used to scan bone samples from 20 patients and predict: bone volume fraction (BV/TV); and trabecular (Tb) and cortical (Ct) thickness (Th), porosity (Po), and spacing (Sp). Results: NIRS scans on both the inner (trabecular) surface or outer (cortical) surface accurately identified variations in bone collagen, water, mineral, and fat content, which then accurately predicted bone volume fraction (BV/TV, inner R 2 = 0.91, outer R 2 = 0.83), thickness (Tb.Th, inner R 2 = 0.9, outer R 2 = 0.79), and cortical thickness (Ct.Th, inner and outer both R 2 = 0.90). NIRS scans also had 100% classification accuracy in grading the quartile of bone thickness and quality. Conclusion: We believe this is a fundamental step forward in creating an instrument capable of intraoperative real-time use. Cite this article: Bone Jt Open 2023;4(4):250–261.